FENOMENA FOTO PREWEDDING DALAM PANDANGAN SYAFI’IYAH (Studi Kasus Pada Akun Instagram @preweddingstyle) - Faiz Redha Alfansuri; Ahmad Ubaidi Hasbillah (Kampus Akademik Publiser, 2024)
The phenomenon of pre-wedding photography has become a trend in Indonesia, undertaken by couples before the marriage contract. However, this practice has sparked debate among Muslims following the Shafi'i school of thought, as it is considered to contain elements of ikhtilat (interaction between non-mahram men and women) and khalwat (seclusion). While some scholars deem it haram, others permit it under the condition that it does not violate Islamic law, such as avoiding khalwat by involving others in the photoshoot and wearing modest clothing that covers the aurat. The rise of digital media has also played a role in spreading this trend, making it crucial to discuss further to provide a clear understanding of the Islamic ruling on pre-wedding photography.